A STUDY OF TECHNOLOGY AVAILABILITY FOR RECYCLING LOW VALUE PLASTIC IN INDONESIA - Soemadijo, Prawitya; Anindita, Faiza; Trisyanti, Dini; Akib, Rangga; Abdulkadir, Mariati; Nizardo, Noverra M.; Rachmawati, Rizka Legita (Journal of Environmental Science and Sustainable Development, 2022)
Plastic has been an essential part of our daily life. However, the increasing plastic consumption has led to an increasing land and water contamination by said plastics. The Indonesian government has set five actions on managing marine plastic debris, one of them is by improving the plastic recycling system. Multilayer plastic was identified as a challenge to the plastic waste recycling. This is because there are differences in properties, such as melting point, which will cause difficulty in mechanical recycling. This study aims to create a mapping of available options to solve problems of low value plastic (LVP) waste in Indonesia and to assess the readiness level of key aspects in implementing the available options. Interviews was done with twelve experts on the field of material or energy recovery from plastic waste, especially LVP, to find the available technology options which include but not limited to their primary features, readiness status and feasibility, and potential market size. The evaluation was based on a set of criteria in technology, environment, social, and economy viewpoints. Three top low hanging options are conversion to plastic lumber, refuse derived fuel (RDF) production, and conversion to plastic products. All the three processes have mature technology and local availability. The challenges include a good branding and marketing strategy to expand market, endorsement, and recognition from government, including recycle content standard and more cost-effective collection. Further investigation has to be done for RDF utilization in industrial boilers. More promotion and introduction of recycled products have to be performed in order to create market to allow a sustainable recycling industry.